2013
DOI: 10.1007/s10552-013-0209-x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease and mouthwash use are risk factors for head and neck squamous cell carcinoma

Abstract: Purpose The purpose of this study was to examine associations between oral hygiene, including history of periodontal disease and mouthwash use, and risk of head and neck squamous cell carcinoma (HNSCC). Methods We measured history of oral hygiene and dental care on 513 HNSCC cases and 567 controls from a population-based study of HNSCC. Logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (95% CI). Results Periodontal disease was associated with a slightly elevated risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 34 publications
4
67
0
3
Order By: Relevance
“…Regarding the frequency of dental visits, to date, 12 studies have been reported. [8][9][10][11][12][13]16,18,[21][22][23][24] Among them, 9 studies reported that lower frequency of dental visits is associated with an increased head and neck cancer risk, [9][10][11][12][13]16,[21][22][23] and our results were consistent with their findings.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the frequency of dental visits, to date, 12 studies have been reported. [8][9][10][11][12][13]16,18,[21][22][23][24] Among them, 9 studies reported that lower frequency of dental visits is associated with an increased head and neck cancer risk, [9][10][11][12][13]16,[21][22][23] and our results were consistent with their findings.…”
Section: Discussionsupporting
confidence: 92%
“…Since we and others have shown that a history of allergy and a history of periodontal disease are independently associated with head and neck cancer risk (and since a humoral response could play a role in disease among those infected with HPV), we examined the data for evidence of a potential interaction between these two medical conditions and high‐risk HPV infection (including HPV16). However, we found no evidence of any significant interaction between history of allergy or history of periodontal disease with HPV infection (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have examined the association between oral hygiene, dental health, and HNSCC. Oral health indicators, including poor dental health, tooth loss, lack of routine dental care by a dentist, and a diagnosis of periodontitis, have been associated with HNSCC . Two studies reported that periodontitis is associated with an increased risk of OPSCC without taking into account HPV status .…”
Section: Introductionmentioning
confidence: 99%